Solve for z 23-3z=-4

Math
23-3z=-4
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Subtract 23 from both sides of the equation.
-3z=-4-23
Subtract 23 from -4.
-3z=-27
-3z=-27
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3z=-27 by -3.
-3z-3=-27-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3z-3=-27-3
Divide z by 1.
z=-27-3
z=-27-3
Divide -27 by -3.
z=9
z=9
Solve for z 23-3z=-4

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top